Organised crime and public sector corruption - Adam M. Tomison
Foreword: In 2006, the Australian Government introduced the Anti-money Laundering and Counter-Terrorism Financing Act 2006 (Cth) which increased regulatory controls over businesses potentially able to facilitate organised criminal activities such as money laundering. The implementation of tougher legislation and associated law enforcement interventions may result in criminal organisations adjusting their tactics in order to continue their activities without detection. In this paper, the risk and potential impact of tactical displacement by organised criminals is discussed with regard to the potential for increased attempts by organised crime groups to corrupt public servants. There is a paucity of research exploring the nature and extent of public sector corruption committed by organised crime groups. This discussion is informed by literature on ‘crime scripts’ originally developed by Cornish (1994) and the 5I’s crime prevention framework developed by Ekblom (2011). Making use of public-source information about the commission of such crimes, as exemplified in two recent corruption cases, some intervention strategies are proposed that may be effective in reducing the risks of corruption of public sector officials by organised crime groups in Australia